Chronic dietary exposure to a glyphosate-based herbicide results in total or partial reversibility of plasma oxidative stress, cecal microbiota abundance and short-chain fatty acid composition in broiler hens - Fréville, Mathias; Estienne, Anthony; Ramé, Christelle; Lefort, Gaëlle; Chahnamian, Marine; Staub, Christophe; Venturi, Eric; Lemarchand, Julie; Maximin, Elise; Hondelatte, Alice; Zemb, Olivier; Canlet, Cécile; et al. (Frontiers in Physiology, 2022)
Glyphosate-based herbicides (GBHs) are massively used in agriculture. However, few studies have investigated the effects of GBHs on avian species although they are largely exposed via their food. Here, we investigated the potential reversibility of the effects of chronic dietary exposure to GBH in broiler hens. For 42 days, we exposed 32-week-old hens to GBH via their food (47 mg/kg/day glyphosate equivalent, GBH, n = 75) corresponding to half glyphosate’s no-observed-adverse-effect-level in birds. We compared their performance to that of 75 control animals (CT). Both groups (GBH and CT) were then fed for 28 additional days without GBH exposure (Ex-GBH and Ex-CT). GBH temporarily increased the plasma glyphosate and AMPA (aminomethylphosphonic acid) concentrations. Glyphosate and AMPA mostly accumulated in the liver and to a lesser extent in the leg muscle and abdominal adipose tissue. GBH also temporarily increased the gizzard weight and plasma oxidative stress monitored by TBARS (thiobarbituric acid reactive substances). GBH temporarily decreased the cecal concentrations of propionate, isobutyrate and propionate but acetate and valerate were durably reduced. The cecal microbiome was also durably affected since GBH inhibited Barnesiella and favored Alloprevotella. Body weight, fattening, food intake and feeding behavior as well as plasma lipid and uric acid were unaffected by GBH. Taken together, our results show possible disturbances of the cecal microbiota associated with plasma oxidative stress and accumulation of glyphosate in metabolic tissues in response to dietary GBH exposure in broiler hens. Luckily, GBH at this concentration does not hamper growth and most of the effects on the phenotypes are reversible.